Designing high-voltage carbonyl-containing polycyclic aromatic hydrocarbon cathode materials for Li-ion batteries guided by Clar's theory1. Issue 37 (7th October 2015) - Wu, Dihua; Xie, Zhaojun; Zhou, Zhen; Shen, Panwen; Chen, Zhongfang
<x xml:space="preserve">Abstract</x> We examined the correlation between the electron delocalization (aromaticity) and the lithiation voltage of carbonyl-containing polycyclic aromatic hydrocarbons by computations.